Intrinsic Cu nanoparticle decoration of TiO2 nanotubes: A platform for efficient noble metal free photocatalytic H2 production - Hejazi, Seyedsina; Mohajernia, Shiva; Wu, Yuhan; Andryskova, Pavlina; Zoppellaro, Giorgio; Hwang, Imgon; Tomanec, Ondrej; Zboril, Radek; Schmuki, Patrik (Electrochemistry Communications, 2019)
In this work, we grow intrinsically Cu-doped TiO2 nanotubes (TiNTs) by self-organizing anodization of Ti–Cu binary alloys. We demonstrate that up to a copper concentration of 1.5 at.% in the alloy, self-ordered Cu2+-doped nanotubes can be grown. Under UV illumination the Cu2+ ion-doped oxide structures can be converted to nanotubes that carry metallic nanoparticles (NPs) uniformly decorated on top of the TiNTs. We investigate the formation of these metallic nanoparticles under UV illumination by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and electron paramagnetic resonance (EPR). The resulting intrinsic copper-doped and decorated TiNTs have a strongly enhanced photocatalytic activity for H2 evolution in comparison to pristine TiNTs. Key is the light-induced conversion of the intrinsic Cu dopant to metallic copper nanoparticles that act as a stable co-catalyst for H2 generation.
CRIS-Team Scopus Importer:2019-09-10
Keywords: Cu doped TiO; Intrinsic copper decoration; Photocatalytic activity; TiO